Funding Shortages Impact on Research and Innovation in TVET Institutions: A Qualitative Analysis - Kamarzaman, N.; Mat Zain, M.N.; Azlin Alisa, A. (Online Journal for TVET Practitioners, 2025)
Technical and Vocational Education and Training (TVET) is essential for developing a skilled workforce in the era of the Fourth Industrial Revolution and globalization. However, funding shortages pose a significant challenge to enhancing research and innovation in Malaysian polytechnics and community colleges. This study employs a qualitative approach, utilizing systematic content analysis and thematic analysis, to explore the impact of insufficient funding on research and innovation activities in TVET institutions. The findings reveal that funding shortages hinder access to research resources, limit the commercialization of innovative products, and negatively affect lecturers’ participation in international research activities. The study highlights five key themes: lack of equipment completeness, limited reference materials, funding shortages for research and innovation, lack of support for commercialization, and the impact on lecturers’ activities. These findings underscore the need for increased funding allocations and strategic measures to ensure the sustainability and advancement of TVET in Malaysia.